Factors Associated with Utilization of Complete Postnatal Care Service in Baglung Municipality, Nepal - Sita Chhetri; Rajani Shah; Laxmi Rajbanshi (Hindawi Limited, 2020)
Background. Postnatal period is six weeks after birth. It is critical but is the most neglected period. A large proportion of maternal and neonatal deaths occur during 48 hours following childbirth. The utilization of the recommended three postnatal checkups within seven days after delivery, which plays a vital role in preventing maternal and neonatal deaths, is low in Nepal. Objective. This study is aimed at identifying the factors associated with the utilization of complete postnatal care (PNC) among mothers. Method. A cross-sectional study was carried out among 318 mothers in wards 1, 2, 3, and 4 of Baglung municipality, Nepal. Data was collected by semi-structured interviews. Descriptive analysis and comparison of characteristics of women/families with complete vs. partial postnatal checkups using multivariable logistic regression were done. Results. Among 314 respondents receiving at least one PNC, 78% had partial and 22% had complete PNC. Relatively advantaged caste/ethnicity- Brahman/Chhetri (aOR=3.18, 95% CI: 1.24-8.12) and Janajati (aOR=2.87, 95% CI: 1.09-7.53) - compared to Dalits, husbands working as a job holder in Nepal (aOR=3.49, 95% CI: 1.50-8.13), and delivery in a private hospital (aOR=11.4, 95% CI: 5.40-24.2) were associated with having complete PNC. Conclusion. Although PNC attendance at least once was high, utilization of complete PNC was low. More focus to mothers from disadvantaged caste/ethnicity, those whose husbands are in foreign employment, and improvement in quality of care in government health facilities may increase the use of complete PNC.